PENGARUH CITRA MEREK DAN STRATEGI PEMASARAN TERHADAP TINGKAT PENJUALAN DI PT. BINA USAHA MANDIRI SEJAHTERA MEDAN - Cindy Prilnes (CV. Armas Suan Sejahtera, 2024)
Marketing strategy is an effort to market a product, be it a product or service, using a certain pattern of plans and tactics so that the number of sales becomes higher. The level of sales is the amount offered by a company by industrial users using distributors. The method used in this study is a survey approach, this type of research is quantitative descriptive and the nature of this research is explanatory research. The population in this study were all employees of PT. Bina Usaha Mandiri Sejahtera Medan, amounting to 84 people with sampling using saturated sampling is 84 people. The method of data collection is done by distributing a list of statements, observations and documentation studies. Variables are measured with a Likert scale. The model of data analysis used to answer hypotheses is multiple regression. The results showed that the brand image and marketing strategy together had a positive effect on the level of sales of PT. Bina Usaha Mandiri Sejahtera Medan. Partially, each variable has an influence on the level of sales and also has a significant effect between the two variables simultaneously on the level of sales of PT. Bina Usaha Mandiri Sejahtera Medan